Humidity control design guide for commercial and institutional buildings (American Society of Heating, Refrigerating and Air Conditioning Engineers, Inc. Atlanta, GeorgiaUS, 2008)
This book is based on designing for humidity control since it is noted that if designers have access to better information, the environment for building occupants all over the world will be better. Human comfort, energy economics, equipment design and construction costs can all be improved by a better understanding of humidity and how it can be controlled. It also aims at providing the tools to meet the challenge of helping every HVAC engineer, architect, building owner, contractor or maintenance engineer, control humidity in a building.